Navigating the Path of Promise: An In-Depth Exploration of Taiwan's Halal Tourism Industry and Policy Initiatives - Mu De, An (Advances in Tourism Studies, 2023)
This study provides a comprehensive examination of Taiwan's emerging halal tourism industry, shedding light on its notable achievements, challenges, and the policy frameworks driving its evolution. Focused primarily on accommodation and restaurants, key sectors in this burgeoning industry, the research explores the impacts of the New Southbound Policy, a governmental initiative aimed at attracting Southeast Asian tourists. Drawing from a diverse range of stakeholders, including representatives from halal tourism, government officials, business owners, and certification bodies, the study employs qualitative methods such as structured interviews and observations to capture nuanced insights. The findings reveal commendable progress in Taiwan's halal tourism sector, particularly in accommodating the needs of Muslim travelers. Government-backed subsidy programs and advocacy for robust policies underline a proactive stance in addressing challenges such as limited halal options in prominent tourist areas. However, the study acknowledges inherent limitations, including regional specificity and language barriers, emphasizing the need for ongoing research to fully comprehend the multifaceted dimensions of this evolving industry. The analysis underscores the influential role of effective tourism policies, showing their pivotal impact on the trajectory of Taiwan's halal tourism. As policies geared towards maximizing social and economic benefits prove instrumental, the study emphasizes the significance of a supportive regulatory framework as a catalyst for success. In conclusion, this research positions Taiwan's halal tourism industry as a promising and resilient player on the global stage. As the industry matures, continuous research and collaborative efforts are advocated to ensure the adaptability, inclusivity, and sustained success of Taiwan's halal tourism initiatives in the ever-evolving global landscape.